2019
DOI: 10.1175/jcli-d-19-0203.1
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the Influence of the Weddell Polynya on the Filchner–Ronne Ice Shelf Cavity

Abstract: Open-ocean polynyas in the Weddell Sea of Antarctica are the product of deep convection, which transports Warm Deep Water (WDW) to the surface and melts sea ice or prevents its formation. These polynyas occur only rarely in the observational record but are a near-permanent feature of many climate and ocean simulations. A question not previously considered is the degree to which the Weddell polynya affects the nearby Filchner-Ronne Ice Shelf (FRIS) cavity. Here we assess these effects using regional ocean model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 61 publications
0
23
0
Order By: Relevance
“…the MITgcm ocean model (Massachusetts Institute of Technology general circulation model) 27,28 , which includes ice shelf thermodynamics and sea ice 2. the Úa ice flow model 29 , which governs the movement and geometry of the ice shelves and ice sheet 3. a custom-built coupler that handles the exchange of information between the two models MITgcm ocean. The ocean component is based on the configuration from Naughten et al 30 , which uses a Weddell Gyre domain with open boundaries at 30 ∘ E and 61 ∘ S. Horizontal resolution is 0.25 degrees scaled by cosine of latitude, and there are 120 vertical levels with 25 m resolution throughout the FRIS cavity. Bathymetry follows Bedmap2 31 with updates in the Filchner Ice Shelf cavity from Rosier et al 32 and the grounded iceberg A23-A as defined by Schaffer et al 33 .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…the MITgcm ocean model (Massachusetts Institute of Technology general circulation model) 27,28 , which includes ice shelf thermodynamics and sea ice 2. the Úa ice flow model 29 , which governs the movement and geometry of the ice shelves and ice sheet 3. a custom-built coupler that handles the exchange of information between the two models MITgcm ocean. The ocean component is based on the configuration from Naughten et al 30 , which uses a Weddell Gyre domain with open boundaries at 30 ∘ E and 61 ∘ S. Horizontal resolution is 0.25 degrees scaled by cosine of latitude, and there are 120 vertical levels with 25 m resolution throughout the FRIS cavity. Bathymetry follows Bedmap2 31 with updates in the Filchner Ice Shelf cavity from Rosier et al 32 and the grounded iceberg A23-A as defined by Schaffer et al 33 .…”
Section: Methodsmentioning
confidence: 99%
“…The ocean component is based on the configuration from Naughten et al 30 , which uses a Weddell Gyre domain with open boundaries at 30 ∘ E and 61 ∘ S. Horizontal resolution is 0.25 degrees scaled by cosine of latitude, and there are 120 vertical levels with 25 m resolution throughout the FRIS cavity. Bathymetry follows Bedmap2 31 with updates in the Filchner Ice Shelf cavity from Rosier et al 32 and the grounded iceberg A23-A as defined by Schaffer et al 33 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results suggest that ice‐shelf/ocean modelers should carefully consider their choice of boundary conditions when running limited area models of the region. In some idealized cases, it has been past practice to use climatological boundary conditions for regional modeling studies (e.g., Hazel & Stewart, 2020; Naughten et al., 2019) but consistency between the boundary conditions and the local forcing is important for realistic representation of inter‐annual variability in re‐analysis focused studies (e.g., Hausmann et al., 2020). More generally, Figures 1a–1f show differences in the observed and simulated temperature and salinity structure of the ASC across different products/time periods.…”
Section: Summary and Further Workmentioning
confidence: 99%
“…Recently, Naughten et al. (2019) showed that offshore polynyas in the Weddell Sea can increase the transport of WDW across the shelf through density changes above the shelf break. Hazel and Stewart (2020) suggest that decreasing the meridional winds by 50% can switch FRIS from a cold to warm state.…”
Section: Introductionmentioning
confidence: 99%